An examination of the factors affecting the judicial assessment of continuity of interest in corporate reorganizations. - Decelles, Michael David (My University, 1983)
While this approach might appear to be sustainable on a theoretical basis, a flaw exists in the reorganization environment which has prevented the attainment of widespread equitable results. That is, given the very high financial stakes involved in reorganizations, taxpayers are too often simply unwilling to risk undertaking what is essentially a subjective and uncertain judicial assessment. This has limited taxpayer access to the judicial alternative and has artificially inflated the authority of the Internal Revenue Service in this area.

A strong economic rationale exists for allowing corporations to alter their legal structures without resulting in unduly excessive taxation--to enhance their efficiency and competitiveness with respect to their overall operations. However, the complexity inherent in the corporate reorganization environment has tended to prevent the enactment of objective statutes which would result in clearly predictable outcomes. Instead, the legislature, by enacting simplistic and rigid statutes, has relied on the judiciary to uphold the spirit of the legislative intent on a case-by-case basis. Furthermore, the primary focus of the judicial assessment of corporate reorganizations focuses on a concept of continuity of interest which involves a substantial continuation of ownership in the surviving corporate entity by the shareholders of the absorbed corporation.

It was the purpose of this study, therefore, to empirically analyze the existing litigation of the continuity doctrine in an attempt to identify variables or factors which comprise the essence of the judicial assessments of continuity of interest. The benefits to be gleaned from such an examination were perceived to be twofold. First, the identified factors might provide a basis for objective statutes which could produce the equitable results of the judicial assessments without producing concomitantly unacceptable levels of subjectivity. And, second, failing the first, it might be possible to instill a greater understanding in taxpayers of the judicial process, thereby increasing the attractiveness of the judicial alternative.
Keywords: Business Administration, Accounting.